NAP1L1 Functions as a Tumor Promoter via Recruiting Hepatoma-Derived Growth Factor/c-Jun Signal in Hepatocellular Carcinoma - Zhang, Ye-wei; Chen, Qian; Li, Bo; Li, Hai-Yang; Zhao, Xue-Ke; Xiao, Yan-yi; Liu, Shu; Zuo, Shi (Frontiers in Cell and Developmental Biology, 2021)
NAP1L1 has been reported to be significantly involved in the carcinogenesis of hepatocellular carcinoma (HCC). Yet, its detailed molecular basis is still to be determined. Based on the analysis of The Cancer Genome Atlas (TCGA) database, NAP1L1 mRNA was found to be upregulated and predicted the poor prognosis initially. Subsequently, consistent with the prediction, the upregulated expression of NAP1L1 mRNA and protein levels was confirmed by quantitative polymerase chain reaction (qPCR), Western blot, and immunohistochemistry assays. Upregulated NAP1L1 protein positively promoted the disease progression and poor prognosis of HCC. In addition, NAP1L1 protein expression was considered as an independent prognostic factor in HCC. Inhibition of NAP1L1 expression by siRNA or shRNA pathway significantly reduced the cell proliferation and cell cycle transformation in vitro and in vivo. Mechanism analysis first showed that the function of NAP1L1 was to recruit hepatoma-derived growth factor (HDGF), an oncogene candidate widely documented in tumors. Furthermore, the latter interacted with c-Jun, a key oncogenic transcription factor that can induce the expression of cell cycle factors and thus stimulated the cell growth in HCC. Finally, transfecting HDGF or c-Jun could reverse the suppressive effects on HCC growth in NAP1L1-suppressed HCC cells. Our data indicate that NAP1L1 is a potential oncogene and acts via recruiting HDGF/c-Jun in HCC.